Formulation and Antioxidant Activity Test of Gel from Fermented Red Pomegranate Peel Juice (Punica Granatum L) - Faizatun Faizatun; Nur Miftahurrohmah; Rosmawati Rosmawati (Fakultas Farmasi Universitas Andalas, 2024)
Red pomegranate (Punica granatum L.) peel has secondary metabolites such as phenolics, flavonoids, and tannins which are known to have antioxidant potential. The purpose of this study was to see the comparison of antioxidant activity of juice before and after fermentation and then formulated into a gel preparation that is physically and chemically stable. Red pomegranate peel juice was dried by freeze drying method and then fermented with Lactobacillus plantarum ATCC 8014 bacteria and measured OD600, pH, and antioxidant activity using DPPH reagent. The results showed that pomegranate peel juice before fermentation had strong antioxidant activity with a value (of IC50 35.64 ± 0.68 ppm) and after fermentation, it was in the very strong category (IC50 8.00 ± 0.01 to 8.11 ± 0.06 ppm); pH before and after (3.96 ± 0.02 and 3.33 ± 0.01). Formula II with juice concentration of 300 x IC50 has the highest antioxidant activity with IC50 values ​​(64.37 ± 1.13 ppm); pH (6.33); spreadability (6.20 ± 0.07); and viscosity (31333.3 ± 577.35 dPas). There was an increase in antioxidant activity of red pomegranate peel juice after fermentation, the resulting gel is physically and chemically stable based on the results of accelerated stability tests for 4 weeks .